One-punch man. 11 - ONE, 1986- (Shonen Jump manga., 2017)
Life gets pretty boring when you beat the snot out of every villain with just one punch. Nothing about Saitama passes the eyeball test when it comes to superheroes, from his lifeless expression to his bald head to his unimpressive physique. However, this average-looking guy has a not-so-average problem--he just can't seem to find an opponent strong enough to take on! --Publisher